AN INTEGRATED UTAUT2 PERSPECTIVE ON DIGITAL BANKING ADOPTION: THE CRITICAL ROLE OF PERSONAL INNOVATIVENESS AND PERCEIVED SECURITY - Anissa Hakim Purwantini; Naufal Afif (Politeknik Negeri Semarang, 2026)
The digitalization of many industries, including banking and finance, is one of the main causes of Indonesia's growing trend in digital banking. Nevertheless, despite this expansion, there are few studies that look at individual traits including security considerations, digital financial literacy, and personal inventiveness. Convenience sampling techniques were used for the survey's sampling, while SEM-PLS was used for the analysis. According to this study, people's intents to use digital banks are positively influenced by performance expectations, favorable conditions, perceived security, and individual inventiveness. On the other hand, the intention to use digital banking services was not significantly affected by effort expectancy or social influence. Furthermore, this study provided evidence suggesting that trust and digital financial literacy do not moderate the influence between behavioral intention and actual usage of digital banks. The findings of this study offer significant implications for digital bank business actors and regulators, particularly within the banking sector of the digital era. Notably, this study represents the first to investigate the antecedents of digital banking service usage based on a theoretical model that comprehensively tests by integrating technology acceptance, individual characteristics, cognitive factors pertaining to digital finance, and digital transaction security.